2018
DOI: 10.3390/ijms19010113
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone as a Modulator of TLR4 and TLR3 Signaling Pathways in Rat Primary Neurons and Astrocytes

Abstract: An antidiabetic drug of the thiazolidinedione class, rosiglitazone (RG) demonstrates anti-inflammatory properties in various brain pathologies. The mechanism of RG action in brain cells is not fully known. To unravel mechanisms of RG modulation of toll-like receptor (TLR) signaling pathways, we compare primary rat neuron and astrocyte cultures stimulated with the TLR4 agonist lipopolysaccharide (LPS) and the TLR3 agonist poly I:C (PIC). Both TLR agonists induced tumor necrosis factor (TNFα) release in astrocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…Similar role of TLR3 activation as an amplifier of the early inflammatory responses have been reported in the kidney and the liver (Patole et al, 2005; Lang et al, 2006). Activation of TLR3 with poly I:C induces a prolonged inflammatory response from cultured astrocytes (Chistyakov et al, 2018), microglia (Dupuis et al, 2016; Yousif et al, 2018), and brain endothelial cells (Johnson et al, 2018). The prolonged inflammatory response induced by TLR3 activation in microglia and astrocytes biologically serves to control or to enhance insidious viral infections such as Chikungunya (Priya et al, 2014) and HIV-1 (Bhargavan and Kanmogne, 2018) and non-viral infections such as Borrelia burgdorferi (Greenmyer et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Similar role of TLR3 activation as an amplifier of the early inflammatory responses have been reported in the kidney and the liver (Patole et al, 2005; Lang et al, 2006). Activation of TLR3 with poly I:C induces a prolonged inflammatory response from cultured astrocytes (Chistyakov et al, 2018), microglia (Dupuis et al, 2016; Yousif et al, 2018), and brain endothelial cells (Johnson et al, 2018). The prolonged inflammatory response induced by TLR3 activation in microglia and astrocytes biologically serves to control or to enhance insidious viral infections such as Chikungunya (Priya et al, 2014) and HIV-1 (Bhargavan and Kanmogne, 2018) and non-viral infections such as Borrelia burgdorferi (Greenmyer et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…An important finding of the present data concerns sex difference in the LPS-induced prostaglandin (PG) synthesis. Although there are still questions concerning the precise roles of various PGs in inflammation or in the resolution of inflammation, there is no doubt that signaling lipids are major regulatory participants of inflammation, developing of neurodegenerative diseases and mood disorders [ 16 , 18 , 30 , 45 ]. We have found only one work with correlations between PGF 2α and PGE 2 synthases, TLR4 and 3β-hydroxysteroid dehydrogenase in a model, where LPS was given in vivo and then the structure and function of the bovine corpus luteum were investigated [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sex differences in the responses of astrocytes to lipopolysaccharide (LPS) as an agonist of toll-like receptors type 4 (TLR4) were demonstrated on the mRNA level [ 13 ]. It has previously been shown that TLR4 activation in astrocytes simultaneously induced, on a protein level, both the pro-inflammatory cytokine tumor necrosis factor alpha (TNFα) and anti-inflammatory cytokine interleukin-10 (IL-10) [ 15 , 16 ]. The modulation of the cyclooxygenase (COX)-2 expression by LPS induces synthesis of various prostaglandins (PG) [ 17 , 18 ], which, modifies both the pro-inflammatory and anti-inflammatory processes, depending on the cellular context [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although most of the work in this field uses LPS in order to stimulate glial cells, mainly microglia, it is known that neurons also express TLR4. Indeed, activation of this receptor leads to the neuronal production of different inflammatory mediators [10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%